Long-term neurological and healthcare burden of adults with Japanese encephalitis: A nationwide study 2000-2015. - Hsuan-Ying Chen (Public Library of Science (PLoS), 2021)
Objective To assess the healthcare utilization, economic burden, and long-term neurological complications and mortality of an adult population with Japanese encephalitis (JE). Methods This study utilized two nationwide datasets in Taiwan: the Notifiable Disease Dataset of confirmed cases from the Centers for Disease Control to identify JE patients, and the National Health Insurance Research Database to obtain patients' healthcare utilization. Survival analyses were performed to identify prognostic factors associated with the all-cause mortality of patients. Results This study included 352 adult cases with JE (aged≥20 years). The mean age of JE patients was 45 years. Stroke (event rate: 3.49/100 person-years) was the most common neurological complication, followed by epilepsy/convulsions (3.13/100 person-years), encephalopathy/delirium (2.20/100 person-years), and parkinsonism (1.97/100 person-years). Among the 336 hospitalized patients at JE diagnosis, 58.33% required intensive care. Among 79 patients who died following JE diagnosis, 48.84% of death events occurred within the year of diagnosis. The medical costs increased considerably at JE diagnosis and subsequent-year costs remained significantly higher than the costs before diagnosis (p<0.05). Having a four-dose JE vaccination (i.e., born after 1976) versus no JE vaccination history (i.e., born before 1963) was significantly associated with lower all-cause mortality (hazard ratio: 0.221 [95% confidence interval: 0.067, 0.725]). Comorbid diabetes and incident epilepsy/convulsion events significantly increased the mortality risk by 2.47- and 1.85-fold, respectively (p<0.05). Conclusion A considerable medical burden associated with JE was observed in affected adults, even in the years following JE diagnosis. Vaccination should be considered to prevent this sporadic, but lethal, viral infection.